Strategic Decisions for Labor Relations Management: A Successful Case in the Construction Industry - Mejia Alvites, Carlos Enrique (2024)
This article analyzes the development of a democratic labor relations model in the construction industry in Peru during the 21st century. Through a qualitative approach, based on semi-structured interviews with union representatives, review of official documents, and journalistic analysis, the strategic decisions made by the Peruvian Chamber of Construction (Capeco), the Federation of Civil Construction Workers of Peru (FTCCP), and the Ministry of Labor and Employment Promotion (MTPE) are identified. These decisions transformed a context of conflict into a framework of cooperation and social dialogue, facilitating collective bargaining and improving working conditions. Three key decisions are highlighted, which were fundamental in consolidating a labor relations system based on mutual trust and industry-wide negotiation. The findings offer lessons for other sectors in building sustainable and productive labor relations.